Intercultural Communication Competence: Unraveling the Role of Cognitive, Affective, and Behavioral Factors - Babao, Joehenson Nino A.; Adiatma, Dicky (Green Publisher, 2023)
Globalization makes the interaction between cultures, different ethnics, national background are inevitable. The competency to communicate across these cultures is crucial more than ever. The purpose of this article is to develop hypotheses regarding the relationships between the cognitive, affective, and behavioral factors in order to explore how these three components affect an individual's intercultural communication competence (ICC). The research is based on online literature sources such as Google Scholar, Mendeley, and other academic online platforms. The research method utilized is library research, utilizing e-books and open-access e-journals. The analysis conducted is qualitative and descriptive. The findings of this article are as follows: 1) Cognitive factors have an influence on intercultural communication competence; 2) Affective factors have an influence on intercultural communication competence; and 3) Behavioral factors have an influence on intercultural communication competence. However this research does not suggest those three components as only factors for ICC and should not be perceived as the exclusive determinants.